Pengaruh Ukuran Perusahaan, Pergantian Manajemen, Ukuran Kantor Akuntan Publik, dan Opini Audit Terhadap Auditor Switching - Arif, Rachmat; Meidiyustiani, Rinny (PT Hakhara Akademia Indonesia, 2024)
The purpose of this research to analyze the effect of company size, management change, KAP size, and audit opinion on auditor switching. The population in this research are banking sub sector companies listed on the Indonesia Stock Exchange in 2017-2021. The method of determining sample in this research used purposive sampling method and produces 45 companies. The analytical method used in this research is logistic regression analysis. The results of the tests in this research prove that the audit opinion has an significant effect on auditor switching. Meanwhile, company size, management change, and KAP size have not significant effect on auditor switching.